Accountability of civil services - Creating an institutional framework - Mathur, B.P. (2012)
Public accountability is the most important component of democratic governance. The political executive delegate their powers to civil servants, who use these discretionary powers to grant licenses and permits, levy taxes, impose fines, execute policies and spend crores of tax payers' money. It is widely felt that public services in India are inefficient and indifferent to people's need. The most important reason for poor performance of public services is lack of accountability due to which public servants can shirk work, evade responsibility and even commit misdemeanour. Accountability of public services may be brought about by creating a proper mechanism. For this, personnel management system should be revamped by linking promotion and career advancement of a public servant with actual performance on job and putting in place an Ethics Code and an effective disciplinary regime. All senior posts should be thrown open to competition so that most competent person in recruited, who should guarantee delivery of high quality services which people value. - Reproduced.
Keywords: Civil service